The functional use of East Dongting Lake, China, by wintering geese - Fox, Anthony D; Lei, Cao; Barter, Mark; Rees, Eileen C; Hearn, Richard D; Hao, Cong Pei; Xin, Wang; Yong, Zhang; Tao, Dou Song; Fang, Shao Xu (Wildfowl, 2013)
A survey and study of geese wintering at the East Dongting Lake National Nature Reserve, China, in February 2008 revealed internationally important numbers of Lesser White-fronted Geese Anser erythropus, Greater White-fronted Geese Anser albifrons and Bean Geese Anser fabilis using the site, as well as small numbers of Greylag Geese Anser anser. Only five Swan Geese Anser cygnoides were recorded, compared with several hundreds in the 1990s. Globally important numbers of Lesser White-fronted Geese spend the majority of daylight hours feeding on short grassland and sedge meadows within the core reserve areas of the National Nature Reserve, and also roost there at night. Greater White-fronted Geese were not studied in detail, but showed similar behaviour. Large numbers of Bean Geese of both serrirostris and middendorffi races showed differing feeding strategies. The small numbers of serrirostris tended to roost and feed in or near the reserve on short grassland, as did small proportions of middendorffi. However, the majority of middendorffi slept within the confines of the reserve by day and flew out at dusk, to nocturnal feeding areas at least 40 km north on the far side of the Yangtze River, returning 40–80 min after first light. In order to safeguard these goose populations, it is essential to optimise the foraging opportunities for geese within the reserve and to understand the feeding habitats exploited by the geese in adjacent and remote areas such as those used by the middendorffi birds north of the Yangtze.